A novel model-based multivariable framework for aircraft gas turbine engine limit protection control - Pang, Shuwei; Jafari, Soheil; Nikolaidis, Theoklis; LI, Qiuhong (Elsevier, 2021)
Control technologies are innovated to satisfy increasingly complicated control demands of gas turbine engines. In terms of limit protection control, a novel model-based multivariable limit protection control method, which is achieved by adaptive command reconstruction and multiple-control loop selection and switch logic, is proposed in this paper to address the problem of balancing smaller thrust loss and safe operations by comparing with widely-used Min-Max logic. Five different combination modes of control loops, which represent the online control loop of last time instant and that of current time instant, is analyzed. Different command reconstructions are designed for these modes, which is based on static gain conversion of amplitude beyond limits by using an onboard model. The double-prediction based control loop selection and switch logic is developed to choose a control loop appropriately by comparing converted amplitude beyond limits regardless of one or more parameters tending to exceed limits. The proposed method is implemented in a twin-spool turbofan engine to achieve limit protection with direct thrust control, and the loss of thrust is improved by about 30% in comparison with the loss of thrust caused by Min-Max logic when limit protection control is activated, which demonstrates the effectiveness of the proposed method.
Keywords: Gas turbine engine; Multivariable control; Onboard prediction; Amplitude conversion; Command reconstruction; Limit protection control